Implementation of Online Learning to Prepare the Youth Generation in the Disruptive Era - Sri Wardani; Sri Haryani; Rosika Harmiasri; Nindy Novita Sari (Universitas Negeri Malang, 2022)
Education is one of the sectors affected by the covid-19 virus. The teaching implementation that was originally face-to-face has been transferred to online learning or distance learning. This study aims to analyze the implementation of online chemistry lectures by both students and lecturers in the 2020/2021 academic year. The subjects of this study consisted of 65 chemistry education students for the academic year 2020/2021. This quantitative descriptive study uses a survey method through a questionnaire conducted online with the help of Google Forms. The results showed that: 1) the implementation of online chemistry lectures was going well, 2) the interaction between lecturers and students and between students was going well, 3) the platforms used were varied and according to their benefits, 4) teaching materials were presented with quality, understanding the material is quite good and the majority of student learning outcomes are in a constant range until it increases, 5) technical constraints of lectures such as signal, cellular data, other activities outside of lectures, and 6) practicum courses cannot be carried out properly because the video provided is not suitable practicum guide.